Does Entry Regulation Hinder Job Creation? Evidence from the French Retail Industry - Marianne Bertrand; Francis Kramarz (Institute for the Study of Labor (IZA), 2002)
Are product market and entry regulation key sources of low employment growth in many European countries? We investigate this question in the context of the French retail trade industry. Since 1974, approval by regional zoning boards has been required for the creation or extension of any large retail store in France. We exploit a unique database that provides time and region specific variation in boards? approval decisions. We show that stronger deterrence of entry by the boards, and the increase in large retail chains? concentration it induced, slowed down employment growth in France.
Keywords: L81; J23; L43; 330; Zoning regulation; retail trade; employment; Markteintritt; Regulierung; Arbeitsnachfrage; Einzelhandel; Frankreich